The effect of stent void area on hemodynamics in cerebral aneurysm - Suriani, Abd Rahman (2009)
The purpose of this study is to develop modeling methodologies to understand how different stent void area alter the aneurysmal flow. Four difference stents design with difference void area were created with suitable geometry for Computational Fluid Dynamics (CFD) analysis. The velocity profile and pressure distribution after installing the device had been identified from the selected stent. These four types of design will be referred as stent type I, II, III, and IV and these stent was tested in an aneurysm model. The simulation of the model was studied under incompressible, Newtonian, viscous, non pulsatile condition. In this study, we need to determine the correlation between stent porous area and blood flow and to determine the flow behavior in stented aneurysm. We found the stent design affected a cerebral aneurysm hemodynamic. The different of stent structural pattern produces the different results of flow field around the stented aneurysm. The minimum velocity had improved after stents insertion and the type IV with less void area results most optimized. Other than that, the peak pressure will also decrease after the stent implantation. As expected, the lowest peak pressure results from stent type IV. The result shows that the stent with the lowest void area gives the best performance.